Pendidikan Kesehatan Pentingnya Membangun Karakter Kepemimpinan Digital Melalui Public Speaking Pada Kelompok Remaja - Hawa, Maria; Aderengke Waang Seik; Yohanes Kornelius Ethelbert; Marianus Kleden; Indriyanti; Veronika Boleng Kelen (Yayasan Inspirasi El Burhani, 2025)
Introduction: The development of information and communication technology has driven changes in aspects of human life, including in education and the formation of leadership character. OSIS as an official organization in schools has a fundamental role in facilitating the development of student leadership potential, in line with the National Education System Law No. 20 of 2003, Perkemendikbud No. 39 of 2008 and No. 62 of 2014. Leadership in the digital era demands communication skills in public, including OSIS members at SMAN 1 Amarasi Selatan, showing low self-confidence and public speaking skills. Objective: This community service aims to improve the understanding and abilities of OSIS members of SMAN 1 Amarasi Selatan regarding the importance of building leadership character in the digital era through public speaking, as well as preparing them to face the challenges of modern leadership. This activity was carried out on May 10, 2025 at SMAN 1 Amarasi Selatan involving 50 OSIS members. Method: The methods used include observation, lectures, simulations of meeting leadership practices, as well as evaluation and feedback. Result: The results show an increase in the knowledge of OSIS members regarding communication leadership in the digital era. Participants demonstrated high enthusiasm and gained strong motivation to develop themselves. Conclusion: In conclusion, this activity successfully built a leadership foundation for the Student Council of SMAN 1 Amarasi Selatan and is expected to serve as a model for other schools in integrating leadership character development and public speaking in the digital era.